ANALYSIS OF CONTINUOUS AMBULATORY PERITONEAL DIALYSIS SERVICE READINESS AT RSUD KOTA BOGOR IN 2023 - Redyardani, Ni Nyoman Diah; Ayuningtyas, Dumilah (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2024)
The availability of health service facilities certainly contributes to one of the success factors in the distribution of health services in Indonesia, including renal replacement therapy (RRT) services. Through Minister of Health Regulation (PMK) No. 8 of 2022, the government ensures that patients with end-stage renal disease (ESRD) receive equal access to RRT. One of the efforts to equalize dialysis services is implementing Continuous Ambulatory Peritoneal Dialysis (CAPD) services. Therefore, RSUD Kota Bogor must prepare for CAPD services in its dialysis installations. This research analyzes the readiness and efforts to provide CAPD services at RSUD Kota Bogor. This study employs a qualitative descriptive-analytical approach to examine the preparation and readiness of RSUD Kota Bogor to provide CAPD services. Most of the CAPD service readiness assessment instruments at RSUD Kota Bogor, based on PMK No. 8 of 2022, have been fulfilled, achieving an 80% compliance rate. However, there is still a need to prepare facilities, infrastructure, and Standard Operating Procedures (SPO) that have not yet been completed so that CAPD services can be effectively implemented.